Water Optics and Water Colour Remote Sensing - Yunlin Zhang (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
Water is irreplaceable natural resources on the planet for people to survival and develop. Declining water quality has become a global issue of significant concern as anthropogenic activities expand and climate change threatens to cause major alterations to the hydrological cycle. Thus, monitoring the physical, chemical, and biological status of rivers, reservoirs, lakes, coastal waters, and oceans is immensely important. Remote sensing has the potential to provide an invaluable complementary source of data at local to global scales. This book-Water Optics and Water Colour Remote Sensing-provides an overview of the current state of the science on water optical properties and water colour remote sensing monitoring. Overall, the book presents a variety of applications at the global scale (with case studies in Europe, Asia, South and North America, and the Antarctic), achieved with different remote sensing instruments, such as hyperspectral field and airborne sensors, ocean colour radiometry, geostationary platforms, and the multispectral Landsat and Sentinel-2 satellites. The book is aimed at a wide audience, ranging from the graduate students, university teachers and the working scientists to policy makers and managers. Efforts have been made to highlight general principles as well as the site-specific application in the field of water optics and water colour remote sensing.